Influential Factors to Financial Management in Chegutu District Secondary Schools of Mashonaland West Province, Zimbabwe - Julius Ndhlovu; Lwazi Sibanda; Joyce Mathwasa (RIRAI Publisher, 2020)
The study explored factors that influence financial management in Chegutu District Secondary Schools of Mashonaland West Province, Zimbabwe. The study was stimulated by the serious financial challenges in secondary schools as characterised by failure to follow laid down procedures, disagreements, inadequate training and lack of knowledge by both school heads and SDC members in managing finances. The interpretive paradigm and qualitative approach guided the study. A case study design was adopted and purposively sampled participants constituted five school heads, five School Development Committee chairpersons, five School Development Committee treasurers and five school bursars. Thematically analysed data was collected through semi-structured interviews and document analysis. The findings revealed that manuals and policy circulars influence the way schools formulate their budgets as they give clear steps that should be followed. It also emerged from the study that the school finance committee is responsible for drawing the school budget after consultation with other stakeholders. It was found that training of school heads, School Development Committee members and bursars influence financial management to a larger extent and there is a very strong relationship between financial management training and effectiveness of financial management in secondary schools. The study concluded that good working relationship among stakeholders and lack of knowledge by both school heads and School Development Committee members in managing school finances greatly influence the way they execute their duty of managing school finances. The study recommends further research that explores strategies that can be established for improving the way schools manage finances.